Corrigendum to "A review on computer vision based defect detection and condition assessment of concrete and asphalt civil infrastructure" [Advanced Engineering Informatics 29(2) (2015) 196–210]. Issue 2 (April 2016) - Koch, Christian; Doycheva, Kristina; Kasireddy, Varun; Akinci, Burcu; Fieguth, Paul
Abstract: In the article [Advanced Engineering Informatics 29(2) (2015) 196–210] in Section 3.2, there is unattributed use of materials from a prior publication, namely Chaiyasarn (2011). This material has been improperly cited and the authors sincerely apologize for this. This corrigendum contains a revised version of Section 3.2 with corrected attributions and citations.